MAKNA SEBUAH KEGAGALAN BISNIS DAN PEMBELAJARAN WIRAUSAHA: SEBUAH PEMBELAJARAN DARI PETANI MUDA DI ERA PANDEMI COVID-19 - Gema Wibawa Mukti; Rani Andriani Budi Kusumo (Universitas Galuh Ciamis, 2021)
The pandemic has disrupted the global economy, including Indonesia as one of the countries affected by the COVID-19 pandemic. This study aims to study young farmers with small scale businesses (small entrepreneurs) who during the Covid 19 pandemic experienced business failures and they tried to create new strategies in doing business or create new businesses as a form of adaptation made by them in the face of the pandemic. This study uses a qualitative and exploratory approach. Informants were chosen purposively, in accordance with the researcher's considerations, namely young farmers who experienced failure in their farming during the Covid 19 pandemic. The informants in this study were taken as many as 5 (five) people, namely young farmers aged 19-40 years and experiencing failure in farming during the covid pandemic 19. The results are expected to contribute to the entrepreneurial learning process from a business failure. From the practical side, the results obtained are expected to provide knowledge for an entrepreneur, that learning is something that comes from a reflection process, so that it can help them to take advantage of their experiences to increase their capacity so that they become better after business failure.